(3SdGM GdeDef aj GdCPcGQs - (3eMeO Hf eMeO Hf Ydj Hf geGe Hf GdGeGe, CHh YHO Gddg,J (B745 (3g` s ((3GHh HcQ Hf EHQGgje Hf GdHOQ GdQedi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdefYe Ydi Ndbg HLejY BdGFg CeG HYO aef Chdi eG GfUQa Edi MaXg GdOYGA eY HQcI GdJCSi hGdEbJOGA s
(3BNQgG (B:s
(3ef bhd Gddg YR hLd ai GdMOjK GdbOSi HGHf BOe dh CJjJfi HbQGH GdCQV NWGjG Ke dbjJfi dGJTQc Hi TjFkG dCJjJc HbQGHgG eZaQI Je GdcJGH s
(3GdcJGH ai hGMO hYTQjf HGHkGs
(3HBNQ GdfSNI SeGY (B767 (3hSeGY BNQ efbhd ef fSNI GdeUfa SfI (B741s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs